From tue civilization of work to the law of work: actors, economy of control and social order in Senegal (1920s-1960s) - (:unkn) unknown (My University, 2016)
Forced labour is one of the most common aspects of colonial rule in Africa and doubtlessly one of the least systematically analyzed and theorized. The vast majority of studies on labour in Africa have emphasized the deep transformations of African societies after the abolition of slavery or the emergence of a urban and masculine wage system in Africa. Nevertheless, few studies have shed light on the political, economic and social effects of coercion at work used on a daily basis by colonial administration in order to control the labour force.The analysis of the system of forced labour in Senegal, from the 1920' to the 1960', ten years after the Senegalese independence, raises three points. First, thinking in the category of forced labour: this work interrogates the implementation and the evolution of the forms of constraints at work by looking at the various representations of work, the discursive and normative processes set in place, as well as its constant reformulation. By doing so, this study aims at overcoming the current historiography, focusing mainly on an institutional approach of forced labour.Secondly, thinking with the category of forced labour: the analysis of the coercive mobilization of the labour force in Senegal underlines that the colonial regime, far from being hegemonic and almighty, oscillated constantly between coercion et powerlessness. The political and economic doctrine of the colonial regime was imposed by arbitrary methods of rule, but was also adjusted and adapted by various power relations within the colonial administration, as well as population who reacted against forced labour.Thirdly, thinking beyond forced labour: this work focuses on the various forms of recruitment in Senegal, even beyond the legal abolition of forced labour in 1946. By overcoming this institutional rupture, it allows us to focus on the evolution of the labour discourse and labour practices in Senegal after the independence. In a context where develo
Keywords: African Research